The teacher 'problem': an analysis of the NSW education policy Great Teaching, Inspired Learning. Issue 5 (3rd September 2017) - Stacey, Meghan
ABSTRACT: This paper seeks to understand the construction of teachers within one New South Wales education policy, querying this construction in relation to both local and international processes and factors. As such, it also looks to contribute to a growing body of international literature which grapples with the role and nature of neoliberal policy development in education more broadly. To accomplish this, the paper analyses Great Teaching, Inspired Learning (GTIL), a policy with wide-ranging and potentially significant ramifications for teachers. Ultimately it is argued that although aspects of neoliberal thinking are evident in the policy, particularities of context have mediated this push. It is suggested that this has led to a particular neoliberalisation of policy that variously targets and supports individual teachers and the systems and structures surrounding them, while the place of GT IL within both local state politics and the global imaginary is questioned.